Commercial and business aspects of alpha radioligand therapeutics - Ostuni, Emanuele; Taylor, Martin R. G. (Frontiers in Medicine, 2023)
Radioligand therapy (RLT) is gaining traction as a safe and effective targeted approach for the treatment of many cancer types, reflected by a substantial and growing commercial market (valued at 7.78 billion in 2021, with a projected value of 13.07 billion by 2030). Beta-emitting RLTs have a long history of clinical success dating back to the approval of Zevalin and Bexxar in the early 2000s, later followed by Lutathera and Pluvicto. Alpha radioligand therapeutics (ARTs) offer the potential for even greater success. Driven by ground-breaking clinical results in early trials, improved isotope availability, and better understanding of isotope and disease characteristics, the global market for alpha emitters was estimated at 672.3 million for the year 2020, with projected growth to 5.2 billion by 2027. New company formations, promising clinical trial data, and progression for many radioligand therapy products, as well as an inflow of investor capital, are contributing to this expanding field. Future growth will be fueled by further efficacy and safety data from ART clinical trials and real-world results, but challenges remain. Radionuclide supply, manufacturing, and distribution are key obstacles for growth of the field. New models of delivery are needed, along with cross-disciplinary training of specialized practitioners, to ensure patient access and avoid challenges faced by early RLT candidates such as Zevalin and Bexxar. Understanding of the history of radiation medicine is critical to inform what may be important to the success of ART–most past projections were inaccurate and it is important to analyze the reasons for this. Practical considerations in how radiation medicine is delivered and administered are important to understand in order to inform future approaches.